The APC/CFZY–1/Cdc20 Complex Coordinates With OMA-1 to Regulate the Oocyte-to-Embryo Transition in Caenorhabditis elegans - Hu, Yabing; Hu, Xuewen; Li, Dongchen; Du, Zhenzhen; Shi, Kun; He, Chenxia; Zhang, Ying; Zhang, Donglei (Frontiers in Cell and Developmental Biology, 2021)
During oocyte maturation and the oocyte-to-embryo transition, key developmental regulators such as RNA-binding proteins coordinate translation of particular mRNAs and related developmental processes by binding to their cognate maternal mRNAs. In the nematode C. elegans, these processes are regulated by a set of CCCH zinc finger proteins. OMA-1 and OMA-2 are two functionally redundant CCCH zinc finger proteins that turnover rapidly during the first embryonic cell division. These turnovers are required for proper transition from oogenesis to embryogenesis. A gain-of-function mutant of OMA-1, oma-1(zu405), stabilizes and delays degradation of OMA-1, resulting in delayed turnover and mis-segregation of other cell fate determinants, which eventually causes embryonic lethality. We performed a large-scale forward genetic screen to identify suppressors of the oma-1(zu405) mutant. We show here that multiple alleles affecting functions of various APC/C subunits, including MAT-1, MAT-2, MAT-3, EMB-30, and FZY-1, suppress the gain-of-function mutant of OMA-1. Transcriptome analysis suggested that overall transcription in early embryos occurred after introducing mutations in APC/C genes into the oma-1(zu405) mutant. Mutations in APC/C genes prevent OMA-1 enrichment in P granules and correct delayed degradation of downstream cell fate determinants including PIE-1, POS-1, MEX-3, and MEG-1. We demonstrated that only the activator FZY-1, but not FZR-1, is incorporated in the APC/C complex to regulate the oocyte-to-embryo transition. Our findings suggested a genetic relationship linking the APC/C complex and OMA-1, and support a model in which the APC/C complex promotes P granule accumulation and modifies RNA binding of OMA-1 to regulate the oocyte-to-embryo transition process.